Description of Blood Pressure and Healthy Lifestyle Behavior among Employees - Glena Dwi Maharani; Aan Nur'aeni; Dadang Purnama (Indonesian Journal of Global Health Research, 2024)
Productive age workers often experience hypertension due to unhealthy lifestyles. Hypertension is known as "The Silent Killer" because it occurs without symptoms (asymptomatic), thus requiring more attention. The purpose of this study is to identify blood pressure levels and healthy lifestyle behaviors among employees at PT Kinaya Multi Energi. The method used in this research is descriptive quantitative, with the population consisting of employees of PT Kinaya Multi Energi. A total of 52 samples were determined using the total sampling technique. The tools used for hypertension screening were a digital sphygmomanometer and a digital body weight scale. The instrument for measuring healthy lifestyle behaviors was a self-efficacy questionnaire for practicing a healthy lifestyle to prevent hypertension. The data analysis used was descriptive quantitative analysis with frequency distribution and percentage. The result of the study shows that The majority of participants in this study experienced increased blood pressure. Respondents without a history of hypertension were mostly in the prehypertension category (32.6%), while a significant number were classified as having stage 1 hypertension (30.4%), and stage 2 hypertension (6.5%). Among respondents with a history of hypertension, most were categorized as having stage 1 hypertension (50%), with a significant number also classified as experiencing prehypertension and stage 2 hypertension (16.7%). Additionally, the majority of respondents have less healthy lifestyle behaviors (57.7%). In conclusion, most respondents experience hypertension and are unaware of it. In terms of healthy lifestyle behaviors, respondents are indicated to have unhealthy behaviors because out of 6 aspects, only 2 aspect supports a healthy lifestyle. This indicates a lack of awareness regarding personal health conditions among the employees.